Волинцевський комплекс ранньослов’янського поселення Обухів 2 - Петраускас, О.В. (Археологія, 2019)
У статті аналізуються матеріали останньої чверті І тис. н. е. найбільш дослідженого ранньослов’янського поселення Обухів 2 з території Середньої Наддніпрянщини. Археологічні дані дозволяють говорити про два види матеріальних комплексів цього поселення. Обидва комплекси належать волинцевській культурі і відображають етапи формування та особливості її розвитку в зазначеному регіоні. Обухівське поселення разом із низкою правобережних ранньослов’янських пам’яток можна співвідносити із літописним племенем полян. В статье анализируются материалы археологического памятника Обухов 2 последней четверти І тыс. н. э. На сегодня это наиболее полно исследованное поселение ранних славян на территории Среднего Поднепровья. Здесь на площади около 9 000 м2 исследовано более 100 объектов, которые датируются I тыс. н. э. и фиксируют последовательное развитие материальной культуры ранних славян в Киевском Поднепровье. К волынцевскому этапу VIII—IX вв. относятся жилища, хозяйственные ямы и наземные очаги. Археологические данные указанного периода позволяют выделить два вида материальных комплексов поселения. Оба комплекса принадлежат волынцевской культуре и отражают этапы ее формирования и развития в данном регионе. Для этого периода характерны полуземлянки срубной конструкции с глинобитными печами усложненных форм; лепные и гончарные горшки «волынцевского» типа; салтовский импорт и др. Комплексы Обуховского поселения третьей четверти I тыс. н. э. позволяют говорить о том, что формирование основных черт волынцевской культуры могло происходить на их основе. Это прослеживается в преемственности заселения территории, конструкциях жилищ и печей, керамическом комплексе и др. Обуховское поселение входит в группу раннеславянских памятников Правобережья Днепра, которые следует соотносить с летописным племенем полян. In the paper the materials of the VIII—IX centuries from the Early Slavic settlement Obukhiv 2 at the territory of the Middle Dnieper are analyzed. At the settlement 9 000 m2 were excavated and more then 100 archaeological objects from the I millenium AD have been explored. The stages of the development of Early Slavs material culture at the Middle Dnieper area are demonstrated. The dwellings, household pits and outdoor fireplaces belong to the Volyntseve phase(VIII—IX c. AD). To this phase the pithouses with log contractions and complicated wattle-and-daub kilns, hand- and weelmade “Volyntseve type” pottery, imported goods from Saltov culture etc. also belong. These materials permit to classify two types of material complexes of this settlement. Both complexes belong to the Volyntseve culture and reflect the stages of its formation and features of development. Complexes of the Obukhiv settlement of the third quarter of the I millenium AD allow us to say that the formation of the main features of the Volyntseve culture could occur on their basis. One can see it in the continuity of the territory settlement, the construction of houses and kilns, the ceramic complex, etc. The Obukhiv settlement, along with a number of Right-Bank Early-Slavic settlements, can be correlated with the annalistic tribe of Polans.